CABI Compendium 2022
DOI: 10.1079/cabicompendium.2676
|View full text |Cite
|
Sign up to set email alerts
|

Acidovorax citrulli (bacterial fruit blotch)

Abstract: This datasheet on Acidovorax citrulli covers Identity, Overview, Distribution, Dispersal, Hosts/Species Affected, Vectors & Intermediate Hosts, Diagnosis, Biology & Ecology, Environmental Requirements, Seedborne Aspects, Natural Enemies, Impacts, Uses, Prevention/Control, Further Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…In turn, Wang et al (2012) note that the A. citrulli and A. oryzae species are closely related and are not easy to differentiate. The comparison of the consensus sequences of the 360 bp band allowed verifying the identity of A. citrulli; therefore, it is concluded that the dark sunken and elongated lesions on the cotyledonal leaves, as well as the black lesions extended from the margin to the base on the true leaves observed in the seedlings of the samples that aligned with A. citrulli, were caused by this bacterium (Osdaghi, 2022) (Table 1, Figure 1), while the dry, yellow and dark lesions are attributed to the other Acidovorax species identified here (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In turn, Wang et al (2012) note that the A. citrulli and A. oryzae species are closely related and are not easy to differentiate. The comparison of the consensus sequences of the 360 bp band allowed verifying the identity of A. citrulli; therefore, it is concluded that the dark sunken and elongated lesions on the cotyledonal leaves, as well as the black lesions extended from the margin to the base on the true leaves observed in the seedlings of the samples that aligned with A. citrulli, were caused by this bacterium (Osdaghi, 2022) (Table 1, Figure 1), while the dry, yellow and dark lesions are attributed to the other Acidovorax species identified here (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…A. citrulli causes seedling blight and bacterial fruit blotch of cucurbits (Burdman and Walcott, 2012). It is a Gram-negative seed-borne bacterium with a high potential for destruction, capable of causing losses of up to 100 % in watermelon nurseries and plantations under favorable environmental conditions of hot weather (temperatures between 28 and 32 °C, relative humidity above 60 %, and sunny days with heavy rains), which promote its multiplication and dissemination (Elizalde-Jiménez et al, 2011;Osdaghi, 2022). Elizalde-Jiménez et al (2011) conducted a NAPPFAST geospatial analysis, which indicated that the southeastern region of Mexico has favorable environmental conditions for the establishment of A. citrulli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation